Peningkatan Keterampilan Menulis Cerpen dengan Model Pembelajaran Discovery Learning pada Siswa Kelas XI SMAN 1 Pangkajene - Nita Ayuni; Sitti Rabiah; Kasma F Amin (Departement of Mathematics Education, 2023)
This research is about the improvement of short story writing skills with the Discovery Learning learning model on class XI students of SMAN 1 Pangkajene, the purpose of this study aims to describe the process of writing short stories of class XI students of SMAN 1 Pangkajene with the Discovery Learning learning model and aims to analyze the results of the improvement of writing short stories with the Discovery Learning learning model on class XI students of SMAN 1 Pangkajene, researchers use action research methods based (Classroom Action Research), data collection techniques used observation sheets, interviews, text and documentation. In this study it can be concluded that the improvement of the Discovery Learning model on the ability to write short stories of students has increased. It can be seen from the results of cycle II learning observations that students become more enthusiastic, active in learning, and able to develop ideas into a short story. In cycle II student learning outcomes reached the KKM as many as 29 people or 93.55%.